Enhancing English Reading Literacy Skill for Javanese Native Speakers: The Predictive Role of Conceptual Scored Vocabulary in Voyager Passport Method - Haryono, Purwo (AL-ISHLAH: Jurnal Pendidikan, 2024)
English reading literacy skills play a crucial role in the academic and professional success of individuals, including Javanese native speakers. This study aims to examine the predictive role of Conceptual Scored Vocabulary in the Voyager Passport Method for enhancing English reading literacy skills among Javanese native speakers. This research is classified as experimental research, with a sample of seventh grade students. The present study employed a quasi-experimental design with random sampling as the sampling method, utilizing two groups pre-post-test. The data collection design employs pre and post-tests administered to both the control and experimental groups. Finally, the collected data was subjected to quantitative analysis using SPSS software. This research result is concluded that Voyager Passport Method can enhance the English reading literacy skill of Javanese Natives Speakers. The findings suggest that the Voyager Passport Method can be an effective instructional approach tailored to the specific needs of Javanese native speakers.